Study of biogas production mechanism from palm mill effluent (POME) - Leong Jing Yong (School of Environmental Engineering University Malaysia Perlis, 2011)
Palm oil mill effluent (POME) contains high chemical oxygen demand (COD) and biological oxygen demand (BOD) as it can pollutes the environment if it was directly discharge without prior treatment. Anaerobic digestion process that used in treat POME wastewater will released methane (CH4) gas and carbon dioxide (CO²) gas as final product which both gases are categories as greenhouse gases that will contribute to the Greenhouse Gases (GHG) Effect. Therefore, this study aims to examine COD removal efficiency of POME at closed anaerobic digestion, study on the production of methane gas at methanogenesis phase and also investigate on the amount of methane gas produce from aech kilogram removal of COD. Operation of this study was proceed with the feed flowrates of 375 mL/d, 450 mL/D, 560 mL/d, 750 mL/d of raw POME wastewater which correspond to Hydraulic Retention Time (HRT)s of 12, 10, 8, 6, and 4 days.